Effects of the psychoeducational intervention program "Live my retirement fully: no to depression and yes to well-being" on subjective experiences of depression in retirees - Nieto-Marín, Constanza Celia (2020)
The objective of the study was to analyze the effects of the psychoeducational intervention program "Live my retirement fully: no to depression and yes to well-being" on subjective experiences of depression in retirees. Qualitative study. Psychoeducational intervention, comprehensive evaluation through case studies with phenomenological interpretation. Six retired older adults over 60 years old, two men and four women, who attend a day-care home for retirees participated as subjects of the study, they were chosen by a theoretical non-probabilistic and convenience sampling method. In-depth individual interviews recorded in audio were executed. A phenomenological analysis was carried out. The results showed that, thanks to the program intervention, retirees recognized the importance of participating in activities and socialize, they also acquired new knowledge, highlighted positive feelings, and emphasized in the importance to keep learning. The effect of the intervention carried out by the program on retirees was positive.